2021
DOI: 10.1111/jace.18178
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong tough zirconia ceramics by defects‐engineering

Abstract: We report the preparation of a category of ultrastrong tough zirconia ceramics by engineering defects using an oscillatory pressure during pressure assisted sintering. The introduced oscillatory pressure enhances the dynamic grain rearrangement, plastic deformation, mass transportation, and pore removal, leading to the formation of pore-free ceramics characterized by the rich coherent grain boundaries among individual mesocrystalline grains with intragranular quasiinterfaces. As a proof of concept, the pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Recently, the studies on a new sintering technique named oscillatory pressure sintering (OPS)/hot oscillating pressing (HOP) (Figure S1a) reveal that the application of oscillatory pressure can induce/enhance plastic deformation of ceramic materials during sintering, so as to accelerate the densification and then full densification as well as inhibited grain growth can be achieved at lower temperature. 18,19 The facilitation of oscillatory pressure to plastic deformation is also confirmed in our previous work on dynamic hot forged ZrO 2 . 20 The OPS has also been employed to sinter binderless WC.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, the studies on a new sintering technique named oscillatory pressure sintering (OPS)/hot oscillating pressing (HOP) (Figure S1a) reveal that the application of oscillatory pressure can induce/enhance plastic deformation of ceramic materials during sintering, so as to accelerate the densification and then full densification as well as inhibited grain growth can be achieved at lower temperature. 18,19 The facilitation of oscillatory pressure to plastic deformation is also confirmed in our previous work on dynamic hot forged ZrO 2 . 20 The OPS has also been employed to sinter binderless WC.…”
Section: Introductionsupporting
confidence: 81%
“…High pressure in high‐temperature environments led to more severe plastic deformation of WC grains, causing the dislocation density within WC grains to rise significantly 32 . The elevated density of intracrystalline dislocations induced a shift in fracture mode, with a large proportion of transgranular fracture modes in the microstructure 33 …”
Section: Resultsmentioning
confidence: 99%
“…32 The elevated density of intracrystalline dislocations induced a shift in fracture mode, with a large proportion of transgranular fracture modes in the microstructure. 33 EDS analysis was performed on the specimen TSS7 (Figure S3). The VC was uniformly dispersed on the surface of the WC matrix, whereas Cr 3 C 2 tended to be dispersed at the grain boundaries between the WC grains (Figure S3B).…”
Section: Mechanical Properties and Toughening Mechanismsmentioning
confidence: 99%
“…In recent years, a new sintering technique, named oscillatory pressure sintering (OPS), has been developed and used to prepare some oxide‐ and non‐oxide‐based ceramics 20 . − 26 It was reported that the introduced oscillatory pressure enhanced the dynamic grain rearrangement, plastic deformation, mass transportation, and pore removal, leading to the formation of pore‐free ceramics 27 . In our previous work, 28,29 the OPS was used to prepare WC ceramics and WC composite ceramics with different carbon sources (including resin powder, carbon block, and graphite oxide nanosheets coming from expanded graphite).…”
Section: Introductionmentioning
confidence: 99%
“…20−26 It was reported that the introduced oscillatory pressure enhanced the dynamic grain rearrangement, plastic deformation, mass transportation, and pore removal, leading to the formation of pore-free ceramics. 27 In our previous work, 28,29 the OPS was used to prepare WC ceramics and WC composite ceramics with different carbon sources (including resin powder, carbon block, and graphite oxide nanosheets coming from expanded graphite). It was found that an addition of 0.3 wt% carbon contributed not only to promoting the densification of WC ceramics but also to inhibiting the formation of W 2 C phase, thus enhancing mechanical properties of such ceramics; especially, the WC ceramics with graphite oxide nanosheets exhibited the optimal hardness and toughness.…”
Section: Introductionmentioning
confidence: 99%